Oxford advanced learner's dictionary of current english - Hornby, A. S.; Wehmeier, Sally (Oxford University Press London, 2009)
Contains 183,500 British and American words, phrases, and meanings, as well as 85,000 examples showing how words are used. This work explains 20,000 word origins on the COMPASS CD-ROM. It includes over 2,000 words and meanings from British and American English, such as offshoring, life coach, sex up, wi-fi.